2013
DOI: 10.5539/ies.v6n6p95
|View full text |Cite
|
Sign up to set email alerts
|

Developing Creative Teaching Module: Business Simulation in Teaching Strategic Management

Abstract: Globalization and liberalization in the business environment have changed the requirements of types and qualities of human capital needed by the corporate sector. In relation to this, business graduates not only need to have theoretical understanding, but they also need to have creative thinking, communication skills and decision making skills based on multidisciplinary knowledge. Simulation game in business education is suggested to fill the gap by exposing students to real business situations. This study eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 29 publications
0
15
1
3
Order By: Relevance
“…Interestingly, the present findings reveal a strong relationship between low self-efficacy and knowledge enhancement in contrast with previous studies (Abdullah et al, 2013;Bandura & Cervone, 1986;Ketelhut, 2007;Meluso et al, 2012;Nicolaides, 2012). This finding is attributed to the fact that HOTS is a multidisciplinary business simulation with teamwork and peer-interaction contributing highly to the experiential learning; it is considered to be of value to curriculum designers and educators in determining the most appropriate stage at which business simulation programmes should be embedded in the curriculum, taking account also of the students' prior knowledge and work experience.…”
Section: Discussion Limitations and Implicationscontrasting
confidence: 86%
See 1 more Smart Citation
“…Interestingly, the present findings reveal a strong relationship between low self-efficacy and knowledge enhancement in contrast with previous studies (Abdullah et al, 2013;Bandura & Cervone, 1986;Ketelhut, 2007;Meluso et al, 2012;Nicolaides, 2012). This finding is attributed to the fact that HOTS is a multidisciplinary business simulation with teamwork and peer-interaction contributing highly to the experiential learning; it is considered to be of value to curriculum designers and educators in determining the most appropriate stage at which business simulation programmes should be embedded in the curriculum, taking account also of the students' prior knowledge and work experience.…”
Section: Discussion Limitations and Implicationscontrasting
confidence: 86%
“…Consequently, self-efficacy has effects on the gathering and enhancement of knowledge. Abdullah et al (2013) and Nicolaides (2012) supported the high influence of student involvement within the learning process in order to enhance the knowledge for the real-life industry and therefore supported the importance of self-efficacy within the context of this research. In addition, Meluso, Zheng, Spires, and Lester (2012) revealed that self-efficacy has been found to be one of the most important determinants of academic achievement.…”
Section: Influence Of Realism On Knowledge Enhancementmentioning
confidence: 79%
“…Quantitative designs adapt from [27][28] were used to find which of the elemen of business simulation that facilitate of business plan preparation and the relationship among them. Students of entrepreneurship courses (114 students) were selected to run business simulation play testing.…”
Section: Methodsmentioning
confidence: 99%
“…The development of this business simulation using Microsoft excel VBA (Visual Basic for Operation) [33]. In this simulation player can play alone or in group [28]. This simulation require player to set up a company, capital, manage resource and manage financial.…”
Section: Background Of the Business Simulationmentioning
confidence: 99%
“…Quantitative designs (Vos and Brennan, 2010;Abdullah et al, 2013) were used to find, which of the element of business simulation that facilitate of business plan preparation and the relationship among them. Students of engineering courses (108 students) were selected to run business simulation play testing.…”
Section: Research Design and Data Collectionmentioning
confidence: 99%